Maciora czy macocha: postkolonialne dylematy Flanna O’Briena - Drong, Leszek (Er(r)go. Teoria - Literatura - Kultura, 2004)
Leszek Drong The Sow or the Stepmother: Flann O'Brien's Postcolonial Dilemmas The essay focuses on the literary and non-literary works by Flann O'Brien (born Brian O'Nolan) explored against the background of Irish history, politics and culture in the aftermath of Ireland's emancipation from Britain in 1921. O'Brien's fiction, as well as his satirical columns contributed to The Irish Times, raise some key postcolonial issues, most notably the role of the Irish language and the prospects of its revival in the Irish Free State. The choice of the continued use of English as the basic means of communication, though apparently politically incorrect, appears to be a necessary evil in a society estranged from its native tongue through centuries of British dominion. O'Brien's writings urge a compromise between two radically polarised positions which emerged in the inter-war period in Ireland: on the one hand, O'Brien appreciates Irish tradition and the Gaelic language; on the other, the progress and well-being of the whole nation necessitate a more pragmatic approach to the postcolonial "burden" (language, tradition, customs, institutions) left behind by the British.